Risk and protective factors for whoonga use among adolescents in South Africa - Teresa DeAtley; Catherine Mathews; Dan J. Stein; David Grelotti; Larry K. Brown; Danielle Giovenco; Millicent Atujuna; William Beardslee; Caroline Kuo (Addictive Behaviors Reports, 2020)
Background: Antiretroviral therapy (ART) is publicly available in South Africa in response to the urgent need to address HIV and AIDS. Off-label use of ARV medication alone or in combination with other substances is known as “whoonga” and “nyaope” in South Africa. Diversion of ARVs for whoonga use is not well understood, especially among adolescents. This secondary analysis explores risk and protective factors for adolescent whoonga use in a community-based HIV endemic setting. Methods: Data on whoonga use were derived from a baseline survey of N = 200 adolescents recruited for participation in a randomized controlled trail to reduce adolescent HIV risk behaviors and depression. Risk and protective factors for adolescent whoonga use were explored using an ecological systems framework using one-way ANOVAs, chi-squared tests and hierarchical regression. Results: Individual level factors increased the odds of whoonga use or known use such as child age OR:1.22 (95% CI, 1.03–1.43), hazardous drug use OR:1.62 (95% CI, 1.02–2.59), and hazardous alcohol OR:1.80 (95% CI, 1.05–3.09). Food insecurity appears to have a slightly protective effect on the odds of whoonga use or reports of use among people adolescents knew OR:0.649 (95% CI, 0.541–0.779). Conclusions: Larger epidemiological studies should expand the surveillance of hazardous alcohol use and illicit drug use, specifically for recreational use of prescription medication. Granular data is warranted to characterize the patters of use, especially among highly vulnerable populations. Future surveillance studies that explore these multi-level relationships are warranted to further understand this phenomenon among teens in South Africa.